Changes of Enzyme Activities and Compositions of Abnormal Fruiting Bodies Grown under Artificial Environmental Conditions in Pleurotus ostreatus - Jang, Kab Yeul (The Korean Society of Mycology, 2005)
This study investigated the biochemical changes of abnormal fruiting bodies grown under artificial environmental conditions in P. ostreatus. Abnormal mushroom growth during cultivation damages the production of good quality mushroom. This study showed that different environmental conditions produced morphological changes in the fruiting bodies of P. ostreatus. The fruiting bodies with morphological changes were collected and examined for differences in biochemical properties, enzyme activities, and carbohydrates composition. The enzyme activities assay showed that glucanase and chitinase activities decreased when the temperature was below or above the optimum cultivation temperature for P. ostreatus. The biochemical compositions of the abnormal mushroom were significantly different from the normal fruiting bodies. It was suggested that the changes in the biochemical composition of abnormal mushroom were caused by the unfavorable environmental conditions during mushroom cultivation.